Evidence-based outcomes of holmium laser enucleation of the prostate. Issue 3 (May 2018) - Large, Tim; Krambeck, Amy E.
Abstract : Purpose of review: Holmium laser enucleation of the prostate (HoLEP) has been a mainstay therapy for the treatment of lower urinary tract symptoms (LUTS) secondary to benign prostate hyperplasia (BPH) for nearly 20 years. We briefly review current and sentinel publications that provide outcomes data after HoLEP. Recent findings: Current literature continues to support HoLEP as a versatile and durable surgical option for men with LUTS secondary to BPH. Despite evidence supporting durable symptom relief beyond 10 years even in large prostate glands, HoLEP is still not widely available to all patients. Concerns surrounding the learning curve of the procedure, high rates of retrograde ejaculation, and transient urinary incontinence seem to persist and limit the adoption of HoLEP by established urologists and residency training programs. Summary: Recent publications continue to show excellent short-term and long-term outcomes after HoLEP, in the categories of voiding function and patient satisfaction. Continued attempts to demonstrate equivalent outcomes of alternate-BPH surgical techniques are being met with renewed efforts by those performing HoLEP to demonstrate equivalent outcomes and patient safety during the learning phase of HoLEP for both mentored and self-directed surgical training.